Association of ventilator-free days with respiratory physiotherapy in critically ill patients with Coronavirus Disease 2019 (COVID-19) during the first pandemic wave. A propensity score-weighted analysis - Privitera, Emilia; Gambazza, Simone; Rossi, Veronica; Santambrogio, Martina; Binda, Filippo; Tarello, Davide; Caiffa, Salvatore; Turrin, Valentina; Casagrande, Carolina; Battaglini, Denise; Panigada, Mauro; Fumagalli, Roberto; et al. (Frontiers in Medicine, 2022)
Background Respiratory physiotherapy is reported as safe and feasible in mechanically ventilated patients with severe Coronavirus Disease (COVID-19) admitted to Intensive Care Unit (ICU), but the short-term benefits remain unclear. Methods We performed a retrospective observational study in four ICUs in Northern Italy. All patients with COVID-19 admitted to ICU and under invasive mechanical ventilation between March 1st and May 30th, 2020, were enrolled into the study. Overlap weighting based on the propensity score was used to adjust for confounding in the comparison of patients who had or had not been treated by physiotherapists. The primary outcome was the number of days alive and ventilator-free (VFDs). The secondary outcomes were arterial partial pressure of oxygen (PaO2)/fraction of inspired oxygen (FiO2) ratio (P/F) at ICU discharge, ICU length of stay, ICU and hospital mortality, and survival at 90 days. The trial protocol was registered on clinicaltrials.gov (NCT 05067907). Results A total of 317 patients were included in the analysis. The median VFDs was 18 days (interquartile range [IQR] 10;24) in patients performing physiotherapy and 21 days (IQR 0;26) in the group without physiotherapy (incidence rate ratio 0.86, 95% Confidence Interval [CI]: 0.78; 0.95). The chance of 0 VFDs was lower for patients treated by physiotherapists compared to those who were not (odds ratio = 0.36, 95% CI: 0.18-0.71). Survival at 90 days was 96.0% in the physiotherapy group and 70.6% in patients not performing physiotherapy (hazard ratio = 0.14, 95%CI: 0.03 - 0.71). Number of VFDs was not associated with Body Mass Index, sex, or P/F at ICU admission for individuals with at least 1 day off the ventilator. Conclusion In patients with COVID-19 admitted to ICU during the first pandemic wave and treated by physiotherapists, the number of days alive and free from mechanical ventilation was lower compared to patients who did not perform respiratory physiotherapy. Survival at 90 days in the physiotherapy group was greater compared to no physiotherapy. These findings may be the starting point for further investigation in this setting.